Navigating Pandemic Moral Distress at Home and at Work: Frontline Workers' Experiences. Issue 4 (31st October 2022) - Miner, S. A.; Berkman, B. E.; Altiery de Jesus, V.; Jamal, L.; Grady, C.
Abstract: Background: During the COVID-19 pandemic, frontline workers faced a series of challenges balancing family and work responsibilities. These challenges included making decisions about how to reduce COVID-19 exposure to their families while still carrying out their employment duties and caring for their children. We sought to understand how frontline workers made these decisions and how these decisions impacted their experiences. Methods: Between October 2020 and May 2021, we conducted 61 semi-structured interviews in English or Spanish, with individuals who continued to work outside of the home during the pandemic and had children living at home. Interviews were recorded, transcribed verbatim, and analyzed using abductive methods. Results: Frontline workers experienced moral distress, the inability to act in accordance with their values and obligations because of internal or external constraints. Their moral distress was a result of the tensions they felt as workers and parents, which sometimes led them to feel like they had to compromise on either or both responsibilities. Individuals felt morally conflicted because 1) their COVID-19 work exposures presented risk that often jeopardized their family's health; 2) their work hours often conflicted with their increased childcare responsibilities; and 3) they felt a duty to their colleagues, patients/customers, and communities to continue to show-up to work. Conclusions: Our findings point to a need to expand the concept of moral distress to include the perspectives of frontline workers outside of the healthcare professions and the fraught decisions that workers make outside of work that may impact their moral distress. Expanding the concept of moral distress also allows for a justice-based framing that can focus attention on the disparities inherent in much frontline work and can justify programmatic recommendations, like increasing paid childcare opportunities, to alleviate moral distress.